Sex Differences in Efficacy and Safety After Left Atrial Appendage Closure: A 4.3-Year Follow-Up Analysis - Chen, Yuyi; Zhang, Yonghua; Qu, Lulu; Chen, Chunyu; Su, Xi; Chen, Yanhong (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Women are related with higher stroke risk and poorer outcome after stroke attack in non-valvular atrial fibrillation (NVAF) patients. The sex differences in efficacy and safety after left atrial appendage closure (LAAC) have remained elusive. This retrospective study aimed to investigate the safety, feasibility and clinical outcomes of LAAC between women and men. Methods: From 2014 to 2018, 395 patients who underwent LAAC in our center were enrolled in this retrospective study. Baseline clinical characteristics, procedural parameters and postoperative follow-up data were collected and compared between women and men. Results: The study included 154 women and 241 men. Compared with men, women were older (68.1±7.9 vs. 64.6±8.8, P<0.01**), with higher CHA2DS2-VASc score (4.0±1.7 vs. 3.0±1.6, P<0.01**). During the mean follow-up duration of 1566 days (4.3 years), there were 39 major adverse cardiovascular events (MACE, including 19 cardiovascular or unexplained deaths, 15 ischemic strokes, and 5 major bleedings) recorded in 34 patients. The overall rate of ischemic stroke was 0.9 per 100 patient-years, and the overall rate of MACE was 2.1 per 100 patient-years. The cardiovascular or unexplained death and major bleeding were comparable between women and men. Compared with men, women had lower rates of ischemic stroke, fatal or disabling ischemic stroke, MACE and fatal or disabling MACE, but none of them reached statistical differences (HR:0.361 P=0.099, HR:0.429 P=0.276, HR:0.600 P=0.170 and HR:0.621 P=0.254 respectively). In the adjusted analyses with multivariate Cox regression models, women had lower fatal or disabling ischemic stroke rate compared to men (HR:0.100, P=0.041). Conclusion: LAAC was feasible and safe for patients of both genders. The ischemic stroke, cardiovascular or unexplained death, and major bleeding were comparable between women and men. However, female was an independent protective factor against fatal or disabling ischemic stroke after LAAC implantation.